Interferência de sistemas de manejo na floresta nacional de Caxiuanã, PA nos atributos físicos e químicos na composição isotópica de solo antropizado - Silva, Rosa de Nazaré Paes da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The use and soil management alters soil character istics, and thus, studies related to pedology, as well as stable isotope associated with agricultural cultivation has been carried o ut over time. This study aimed to evaluate through the physical, chemical and isotopic composition of δ 13 C and δ 15 N changes caused by different tillage systems on the effective depth layer in anthropogenic soils. The experimental design was completely randomized in a 3x4 factorial design, 3 - factor use system (Terra Preta formed on Ultisol under Secondary Forest - TPI /ARGI FS ; Ultisol under Capoeira - ARGI CP and Ultisol under Plantation - ARGI RC ) and 4 - depth factor (0 to 5, 5 to 10, 10 to 20 and 20 to 30 cm) using 9 replicates. In each system was performed characterization, classification, collection and analysis of 108 composite samples. The variables studied were: particle size, carbon storage, isotopic composition of δ 13 C, δ 15 N, C and N content, C/N ratio, pH in H 2 O and ClCa 2 , soil organic matter, phosphorus, potassium, calcium, magnesium, sodium, boron, copper, manganese, iron, zinc, aluminum, hydrogen and aluminum, sum of base cation exchange capacity, capacity exchange cation effective base saturation index and the index of aluminum saturation. To evaluate the results we used the mean test (Tukey test at 5% si gnificance). It was observed that the scuffed areas C and N showed higher values at a depth of 20 to 30 cm, justifying its occurrence due to manual tilling soil litter layer incorporating deeper. Anthropogenic soils under Secondary Forest (TPI/ARGI FS ) present with low acidity and high levels of phosphorus, potassium, calcium and sodium. It is worth noting that the levels of potassium are significantly lower, which accuses the deficiency of TPI/ARGI FS for this nutrient. Significant amounts of magnesium were found in anthropogenic soil under plantation (ARGI RC) than justified by the ...

O uso e manejo do solo altera as características dos solos, e com isso, estudos relacionados à edafologia, bem como isótopo estável associado ao cultivo agrícola, tem sido realizado ao longo do tempo. O presente trabalho teve como objetivo avaliar através dos atributos físicos, químic os e na composição isotópica do δ 13 C e δ 15 N as alterações causadas por diferentes sistemas de manejo na camada da profundidade efetiva em solos antropizados. O delineamento experimental foi inteiramente casualizado em esquema fatorial 3x4, sendo 3 - fator sistema de uso (Terra Preta de Índio formada sobre: Argissolo Amarelo sob Floresta Secundária – TPI/ARGI FS; Argissolo Amarelo sob Capoeira – ARGI CP e Argissolo Amarelo sob Roça – ARGI RÇ) e 4 - fator profundidade (0 a 5; 5 a 10; 10 a 20 e 20 a 30 cm), co m 9 repetições. Em cada sistema foi realizada a caracterização, classificação, coleta e análise de 108 amostras compostas. As variáveis estudadas foram: granulometria, estoque de carbono, composição isotópica de δ 15 N e δ 13 C, teor de C e N, relação C/N, pH em H 2 O e ClCa 2 , matéria orgânica do solo, fósforo, potássio, cálcio, magnésio, sódio, boro, cobre, manganês, ferro, zinco, alumínio, hidrogênio e alumínio, soma de bases, capacidade de troca de cátions, capacidade de troca de cátions efetiva, índice de sat uração por bases e o índice de saturação por alumínio. Para avaliação dos resultados foi utilizado o teste de média (Tukey a 5% de significância). Observou - se que nas áreas de roçado o C e o N apresentaram valores significativos na profundidade de 20 a 30 cm, devido ao revolvimento manual do solo, incorporando a liteira na camada mais profunda. Os solos antropizados sob Floresta Secundária (TPI/ARGI FS) apresentaram - se com baixa acidez, altos teores de fósforo, potássio, cálcio e sódio e baixos teores de po tássio. Valores ...
Keywords: Isótopos estáveis; Solos - Fertilidade; Ecossistemas; Solo adequado para agricultura; Stable isotopes